Influência da época de plantio, tamanho da muda e idade da planta para a indução floral no abacaxi "Smooth Cayenne" no recôncavo baiano - Reinhardt, Domingo Haroldo Rudolfo Conrado (1984)
The influence of time of planting, size of the planting material and floral induction at different plant ages on growth, development, fruit yield and quality of 'Smooth Cayenne' pineapple was observed in work conducted in the Recôncavo Baiano, Cruz das Almas, Bahia, from January 1980 to June 1983. [...]